Development of learning modules with the concept of religious moderation to facilitate students' mathematical literacy skills - Mubarak, Ashar; Nur, Fitriani; Baharuddin, Baharuddin; Idris, Ridwan; Abrar, Andi Ika Prasasti (Universitas Islam Negeri Raden Intan Lampung, 2025)
Radicalism in religious life has become a serious problem, leading to the emergence of the term religious moderation in society. On the other hand, the low level of mathematical literacy in higher education also requires attention. This study aims to develop a learning module based on religious moderation to improve students' mathematical literacy. The module was developed using the ASSURE model. The validation results by experts showed a score of 3.814, categorized as